Legal Protection Against Health Workers in Taking First Aid Medical Measures - Julianto Jover Jotam Kalalo; Chyntia Novita Kalalo (Faculty of Law, Musamus University, 2018)
Health workers are a noble job, this is because they are the foremost fighters in terms of health services. Health workers are part of a health service that needs legal protection in carrying out their duties and responsibilities as public health servants. In carrying out its duties, health workers are given the authority to carry out health service efforts in accordance with applicable regulations. This authority in the form of legal rules that can be used as a guideline or basis for health workers to carry out a medical action in a case of health they face. Health workers in taking first aid medical actions must obtain a protection in carrying out their performance as health workers in accordance with Tupoksi and oaths of appointment as health workers. In the oath of appointment as a health worker in taking the first action is regulated in the rules of the code of ethics and hospital regulations and others. Efforts that can be made by the government in this case the Health Office, Hospital and Regional Government are making a rule that can regulate the implementation of the first level medical action in dealing with patients inside the hospital or in an accident.